Epidemiologic, Clinical and Immunological Consequences of Co-Infections during Canine Leishmaniosis - Erin A. Beasley (MDPI AG, 2021)
Canine leishmaniosis (CanL) is a vector-borne, parasitic disease. CanL is endemic in the Mediterranean basin and South America but also found in Northern Africa, Asia, and the U.S. Regions with both competent sand fly vectors and L. infantum parasites are also endemic for additional infectious diseases that could cause co-infections in dogs. Growing evidence indicates that co-infections can impact immunologic responses and thus the clinical course of both CanL and the comorbid disease(s). The aim for this review is to summarize epidemiologic, clinical, and immunologic factors contributing to eight primary co-infections reported with CanL: Ehrlichia spp., Anaplasma spp., Borrelia spp., Babesia spp., Trypanosoma cruzi, Toxoplasma gondii, Dirofilaria immitis, Paracoccidioides braziliensis. Co-infection causes mechanistic differences in immunity which can alter diagnostics, therapeutic management, and prognosis of dogs with CanL. More research is needed to further explore immunomodulation during CanL co-infection(s) and their clinical impact.